Walsh functions and Gray codes - Білецький, Євген Анатолійович (Ukrainian Information Security Research Journal, 2013)
The paper developed a method of synthesis of symmetric systems Walsh based on their indicator matrices (the method is defined as a direct challenge Walsh) and calculating the indicator matrix of these systems (the inverse problem Walsh). The order of the indicator matrix is a logarithmic function of the base 2 of the binary-rational order systems Walsh. Introduced matrix forms a complete set of simple Gray codes. The set contains the classical direct and inverse transform (called left-Gray codes) and a new class of right transformations Gray, supplemented by the operator to maintain the original codeword (identity matrix) and the matrix inverse permutation. Proposed composite Gray codes, which are the multiplicative combination of an arbitrary set of simple codes. The relationship of simple and symmetrical composite Gray codes with indicator matrices of appropriate systems of Walsh functions